TEKNIK METODE BACK ROLLING MASSAGE DAN PIJAT WOOLWICH EFEKTIF MENINGKATKAN PRODUKSI ASI PADA IBU POST SEKSIO SESAREA DI RS HERMINA - Suryani Hartati; Melli ka Rosita; Retno Winarti (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2024)
After giving birth by caesarean section, the mother does not undergo Early Initiation of Breastfeeding in the first hour after the birth of the baby which results in the production of breast milk not being stimulated or the baby's sucking reflex being absent which affects the release of breast milk.. The purpose of this scientific paper is to describe the effect of rolling back massage and woolwich massage techniques on increasing breast milk production in 5 Mrs. S 33 years old P1A0 with post sectio cesarea indications of cephalopelvic disproportion. This research method uses case studies. The research was conducted on May 1 - 3, 2024 at Hermina Hospital Jatinegara. Nursing actions taken are rolling back massage techniques and woolwich massage. which was carried out for 2 days every morning and afternoon for 20 minutes, it was found that the increase in breast milk production. Evaluation of breast milk out, smoothly. Nurse recommendations are expected to carry out non-pharmacological therapy rolling back massage and woolwich massage in post section caesarea patients to increase breast milk production.